Statistical analysis and filter design for conducted emission noise - Zainal, Mohd Shamian (2003)
Electromagnetic compatibility (EMC) is the ability of equipment and system to function as intended without degradation or malfunction in their intended operational electromagnetic environment. Further, the equipment or system should not adversely affect the operation of, or be adversely affected by any other equipment. There are two categories of Electromagnetic Compatibility; (1) Electromagnetic Susceptibility (EMS) (2) Electromagnetic Interference (EMI). EMS and EMI can be further divided into two categories namely radiated and conducted. Conducted emission is the unwanted currents that are produced by electronic and electrical equipments emitted through the power lines. The main sources of conducted emission are common mode current and differential mode current. These currents will interfere with any equipments that are connected to the same power lines. EMC standards pertaining to the conducted emission (such as EN55014) define the limit lines that should not be exceeded or the product cannot be marketed. In order to avoid non-compliance to the standards, most electronic/electrical equipments have power line filter installed into them. However, these filters are not effective enough because they were designed without considering the emission currents characteristics. This project proposed a method to improve the design of a power line filter by analyzing the characteristic of the emission current noise. The results from the statistical measurements can be used to identify the range of frequencies where most of the noises are located. Eighty four blenders were used as a sample to identify the characteristic of the noise. It was found out that the conducted emission exceed the limit line from 150kHz to 1MHz by 5dB and by lOdB at frequencies from 1MHz to 30MHz. A butterworth filter with cut-off frequency of 70.56kHz and bandwidth from 0 to 120kHz was designed. The parameters of the filter were based on the statistical data of the conducted emission. The test result shows that the filter attenuate the noise about 42dB at frequency range of 150kHz to 10MHz and lOdB at frequency range from 10MHz to 30MHz. The low attenuation at frequencies from 10MHz to 30MHz is due to the existence of capacitive and skin effect. A better filter can be achieved if a higher quality component is used in the fabrication.